Orexin Receptor-1 in the Rostral Ventrolateral Medulla Mediates the Antihypertensive Effects of Electroacupuncture - Tan, Ying-Ying; Fang, Ling; Yao, Fan-Rong; Cao, Dong-Yuan; Zhang, Qi (Frontiers in Neuroscience, 2019)
Electroacupuncture (EA) has been used to treat numerous diseases, including hypertension. This study aimed to investigate the long-term effect and underlying mechanisms of EA stimulation at the LI11 point on the hypertension and sympathetic nerve activity in two-kidney, one-clip (2K1C) hypertensive rats. EA (0.1–0.4 mA, 2 and 15 Hz) was applied to the acupoints LI11 overlying the deep radial nerve once a day for 6 weeks. The mean arterial pressure (MAP) and heart rate (HR) were determined by radiotelemetry, and the sympathetic nerve activity was evaluated by telemetric analyses of the low-frequency component of blood pressure (BP) and by plasma epinephrine and norepinephrine levels. The results showed 6 weeks of EA significantly lowered the increased BP effectively, inhibited the enhanced sympathetic nerve activities and attenuated cardiac hypertrophy in 2K1C hypertensive rats. The level of orexin receptor-1 (OX1R) in the rostral ventrolateral medulla (RVLM) after EA treatment was markedly reduced in 2K1C rats, while there was no difference in the RVLM expression of orexin receptor-2 (OX2R) in 2K1C and 2K1C+EA rats. Moreover, the increased pressor and depressor responses to microinjection of orexin A or OX1R antagonist SB408124 into the RVLM of 2K1C rats were significantly blunted by the EA treatment. These findings suggest that BP-lowering effect of EA on renovascular hypertension may be through inhibition of central sympathetic activities and modulation of functional orexin receptors in the RVLM.